2019
DOI: 10.1002/lpor.201900065
|View full text |Cite
|
Sign up to set email alerts
|

A Spin‐Encoded All‐Dielectric Metahologram for Visible Light

Abstract: Dielectric materials that are low‐loss in the visible spectrum provide a promising platform to realize the pragmatic features of metasurfaces. Here, all‐dielectric, highly efficient, spin‐encoded transmission‐type metaholograms (in the visible domain) are demonstrated by utilizing hydrogenated amorphous silicon (a‐Si:H). In comparison to previously reported visible metaholograms based on TiO2 and other dielectric materials, all‐dielectric metasurfaces provide a cost‐effective more straightforwardly fabricated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

8
2

Authors

Journals

citations
Cited by 123 publications
(76 citation statements)
references
References 37 publications
0
76
0
Order By: Relevance
“…In addition to color filters, holography is another coloration application of metasurfaces. In metaholograms, each meta-atom on the metasurface is designed to resonate the incident light at a certain visible frequency, so the desired image can be displayed [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. K. Kim and G. Yoon have also shown that metaholograms can be realized at a large scale using nanoimprint lithography (NIL) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to color filters, holography is another coloration application of metasurfaces. In metaholograms, each meta-atom on the metasurface is designed to resonate the incident light at a certain visible frequency, so the desired image can be displayed [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. K. Kim and G. Yoon have also shown that metaholograms can be realized at a large scale using nanoimprint lithography (NIL) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…18 In addition, in optical devices based on dielectric metasurfaces, the refractive index n of the dielectric is not large, so a nanostructure with high aspect ratio (AR) is often required. For example, titanium dioxide (TiO 2 ) or gallium nitride (GaN) require a high AR of 10 to 15, and amorphous silicon requires an AR of 4.7; 19 such high values complicate nanofabrication and thus limit further device miniaturization. A Mie resonator has been implemented by stacking atomically thin transition-metal dichalcogenide (TMDC) materials.…”
Section: Materials Platforms For Metasurfacesmentioning
confidence: 99%
“…The physical mechanism of the MSs exploits adjustment of wave phase shifts, unlike bulk MTMs, in which waves are manipulated by changing the effective parameters of the material. MSs can be used in applications such as anomalous reflection and refraction [132,133], polarization conversion [134,135], focal lenses [136][137][138] and holograms [139][140][141][142]. MSs are based on the generalized Snell's law with phase discontinuity [143].…”
Section: Elastic Metasurfacesmentioning
confidence: 99%